2012
DOI: 10.1371/journal.pone.0043991
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Natural Variation for Seedling Traits and Their Link with Seed Dimensions in Tomato

Abstract: The success of germination, growth and final yield of every crop depends to a large extent on the quality of the seeds used to grow the crop. Seed quality is defined as the viability and vigor attribute of a seed that enables the emergence and establishment of normal seedlings under a wide range of environments. We attempt to dissect the mechanisms involved in the acquisition of seed quality, through a combined approach of physiology and genetics. To achieve this goal we explored the genetic variation found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
72
2
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 88 publications
11
72
2
8
Order By: Relevance
“…Similar associations were also obtained between DFST and DFTT with WS, which suggested that seed weight showed a positive effect on the development time of sympodial units formed after the floral transi- tion due to gene linkage. In this regard, similar effects caused by the seed size and weight in tomato seedlings were reported by Khan et al (2012), who concluded that effects on seedling growth were due to the genetic variation in the amount of food reserve (starch) and maternal effects. In addition to seed weight, various factors such as the number of leaves produced before the first inflorescence, length of floral development, light intensity and temperature have been reported to affect the floral transition (Dieleman and Heuvelink, 1992;Samach and Lotan, 2007;Sumugat et al, 2010).…”
Section: Different Genetic Pathways Controlling Earlinesssupporting
confidence: 71%
See 1 more Smart Citation
“…Similar associations were also obtained between DFST and DFTT with WS, which suggested that seed weight showed a positive effect on the development time of sympodial units formed after the floral transi- tion due to gene linkage. In this regard, similar effects caused by the seed size and weight in tomato seedlings were reported by Khan et al (2012), who concluded that effects on seedling growth were due to the genetic variation in the amount of food reserve (starch) and maternal effects. In addition to seed weight, various factors such as the number of leaves produced before the first inflorescence, length of floral development, light intensity and temperature have been reported to affect the floral transition (Dieleman and Heuvelink, 1992;Samach and Lotan, 2007;Sumugat et al, 2010).…”
Section: Different Genetic Pathways Controlling Earlinesssupporting
confidence: 71%
“…Recently in tomato, several studies have reported the influence of epistasis on fruit shape, locule number, seed size and fruit weight during the process of domestication (Lippman and Tanksley, 2001; van der Knaap et al, 2002;Khan et al, 2012). In few studies have the epistatic interactions between the components of earliness and fruit weight been examined, and it is equally unclear if tomato earliness is controlled by a single genetic mechanism or something more complex.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that seed size is positively correlated with growth of the seedling primary root (Elwell et al 2011;Khan et al 2012). One possible explanation for how reduced seed size increases penetrance of the pickle root phenotype is that the derepression of embryonic master regulators that occurs in pkl seedlings (Henderson et al 2004;Li et al 2005) is more likely to result in adoption of the pickle root phenotype in slower-growing roots.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that although our data demonstrate that manipulation of seed size is sufficient to alter penetrance of the pickle root phenotype, our data do not preclude the possibility that loss of PKR2 enhances pickle root penetrance in small seeds via a mechanism that acts in addition to the effect on seed size. It has previously been shown that seed size is positively correlated with growth of the seedling primary root (Elwell et al 2011;Khan et al 2012). One possible explanation for how reduced seed size increases penetrance of the pickle root phenotype is that the derepression of embryonic master regulators that occurs in pkl seedlings (Henderson et al 2004;Li et al 2005) is more likely to result in adoption of the pickle root phenotype in slower-growing roots.…”
mentioning
confidence: 99%
“…Seed quality and supply impact the volume and nutritional value of the crops 13. Seed systems in Africa are generally underdeveloped, with the majority of smallholder farmers procuring seed through informal systems, and therefore commercial seed companies making only minor contributions 14.…”
Section: Farmingmentioning
confidence: 99%